Laparoscopic Surgery - Malik, Arshad M. (IntechOpen, 2017)
Laparoscopic surgery developed as the most element change ever in the history of surgery. The approach of this method is no more a late headway. The history goes back three decades now when appendectomy was initially performed laparoscopically in 1983. It was then polished by not very many specialists, and there was a moderate move of the method from traditional open surgery to laparoscopic surgery. Hesitance to take in an absolutely new method, absence of facilities, and appropriate training were main considerations ruining its direction. After an underlying hindered period came a sudden ascent in the worldwide preoccupation of the consideration toward this novel strategy. There was an aggregate move from open to laparoscopic surgery in a large portion of the focuses with an expanding rundown of operations being performed laparoscopically. This book is intended to bring forward the very many advancements in the field of laparoscopic surgery. There are many valuable contributions from eminent laparoscopic surgeons ranging from diagnostic to therapeutic procedures performed by this technique. I hope it will benefit the trainee surgeons as well as the experienced alike. Suggestions and positive criticism are more than welcome.